Morphological , textural and sensory property of bun formulated with different particle size of cornlettes powder - Husin, Wan Nur Suriati (2015)
Cornlettes or immature com which is one of the commonly consumed vegetable by Malaysian populace contains high dietary fiber in dried form. Presently, cornlettes have been introduced in enhancing nutritional qualities of baked-based products. This study aims to investigate the influence of different particle size (45, 125 and 250 pm) of cornlettes on the quality of bun which covering morphological characterization, physicochemical, textural property and sensory evaluation. Scanning electron microscopical observation showed that at higher magnification, there are compact particles of wheat flour and dietary fibers especially bun formulated with larger particle size of comlettes. In addition, microstructure of comlettes with oily particles intact were clearly seen. Dietary fiber of comlettes was seen able to absorb fat molecules. For texture profile analysis (TPA), as particle size increases (45,125 and 250 pm), the decreasing of hardness (1.45 kg to 1.32 kg), gumminess (1.74 kg to 0.98 kg) and chewiness (1.74 kg to 0.98 kg) compared to control were observed. In sensory evaluation, bun formulated with 250 pm particle size of comlettes was preferred by sensorial panellists eventhough not significant with other treatments. Among 3 different particle sizes of comlettes added in bun formulation, bun added with 250 pm particle size of comlettes resulted as less firmness (1.32 kg), gumminess (0.98kg) and chewiness (0.98kg) compared to other treatments. In brief, bun added with 250 pm particle size of comlettes is recommended in the preparation of high fibre and palatable bun.